The Responsible Administrator: An Approach to Ethics for the Administrative Role - Cooper, Terry L. (San Francisco: Wiley, 2012)
"This is the substantially revised edition of the classic book The Responsible Administrator--the book that has guided professionals and students alike as they grapple with the challenges of making ethical, responsible decisions in real world situations. This fifth edition has been adapted to reflect current thinking and includes a new introduction as well as updated information on coping with demands for accountability, cases and examples, research references, and an examination of current issues relevant to administrative ethics. In addition, the design approach has been developed further in both the introduction and the new concluding chapter"--
Machine generated contents note: Preface to the Sixth Edition Acknowledgments The Author 1 Introduction 2 Understanding Ethical Decision Making Part One: Ethics for Individual Administrators 3 Public Administration in Modern and Postmodern Society: The Context of Administrative Ethics 4 Administrative Responsibility: The Key to Administrative Ethics 5 Conflicts of Responsibility: The Ethical Dilemma Part Two: Ethics in the Organization 6 Maintaining Responsible Conduct in Public Organizations: Two Approaches 7 Integrating Ethics with Organizational Norms and Structures 8 Safeguarding Ethical Autonomy in Organizations: Dealing with Unethical Superiors and Organizations Part Three: The Design Approach 9 Applying the Design Approach to Public Administration Ethics 10 Conclusion: Responsible Administration References Index.
Keywords: Civil service ethics; Government executives -- Professional ethics